Effect of Taichi Softball on Function-Related Outcomes in Older Adults: A Randomized Control Trial. (6th April 2017) - Lou, Lin; Zou, Liye; Fang, Qun; Wang, Huiru; Liu, Yang; Tian, Zuguo; Han, Yunpeng
Abstract : The purpose of this present study was to examine the effect of Taichi softball (TCSB) on physical function in Chinese older adults. Eighty Chinese older adults were randomly assigned into either an experimental group experiencing four 90-minute TCSB sessions weekly for seven consecutive weeks or a control group. At baseline and 7 weeks later, all participants were asked to perform physical functional tests for both lower and upper limbs. Multiple separate Analyses of Variance (ANOVA) with repeated measures were applied to evaluate the effects of TCSB on function-related outcomes between baseline and postintervention in the two groups. The findings indicate that a short-term and intensive TCSB training program does not only improve low limb-related physical function such as dynamic balance and leg strength, but also strengthen upper limb-related physical function (e.g., arm and forearm strength, shoulder mobility, fine motor control, handgrip strength, and fine motor function). Health professionals could take into account TCSB exercise as an alternative method to help maintain or alleviate the inevitable age-related physical function degeneration in healthy older adults. In addition, researchers could investigate the effect of TCSB exercise on physical function in special populations such as patients with different chronic diseases or neurological disorder (e.g., Parkinson's disease).